Pergeseran Sistem Kepemimpinan Tradisional pada Masyarakat Adat Kampung Ayapo Kabupaten Jayapura - I Made Sudayasa; Simon Abdi K. Frank; Enos H. Rumansara (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
This article aims to describe and identify the shift in traditional leadership in Kampung Ayapo. This research use desciptive qualitative approach. The results showed that the ondoafi position was a patrilineal lineage, the implication being that power or position was acquired. An ondoafi has a very important position in the village community so an ondoafi must be able to play more roles in the leader of his group. Because the requirements to become ondoafi are quite heavy to fulfill so that the person who appears as the leader of ondoafi is really a person who not only has a hereditary relationship with the ancestors of the village founder, but also has certain qualities that are demanded as a leader. When there was contact with outsiders, traditional shifts began to appear, the change began when missionaries came to Ayapo village with new teachings that significantly changed their beliefs and beliefs, strengthened again during the second world war which also brought the same teachings. . its peak when the formation of the village in 1979 (now kampong) brought about a considerable shift in the role, authority, function and power of ondoafi as traditional leaders in Ayapo Village.